2007
DOI: 10.1080/09297040600837362
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in Memory Function, and its Relationship to Academic Success, at 24 Months Following Pediatric TBI*

Abstract: While a number of research papers have reported findings on memory deficits following traumatic brain injury (TBI), only limited studies have monitored the recovery of these skills over time. The present study examined memory ability and its effect on academic success in a group of children who had sustained a mild, moderate, or severe traumatic brain injury (TBI). Results showed that the severe TBI group exhibited greater deficits on memory tasks, irrespective of modality, in the acute, 6-, 12-, and 24-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 45 publications
3
31
0
3
Order By: Relevance
“…Ewing-Cobbs et al (2004) employed a transformation span (Digit Span Backward) task to assess the CE, which did not predict performance on arithmetic and reading comprehension after controlling for the duration of impaired consciousness and SES. Catroppa and Anderson (2007), who examined the storage components only, did not find an association between the performance of children with mild-to-severe TBI on measures of PL and VSSP and tests of reading and mathematics. Further research examining each of the components of WM and their contribution to different academic skills after pediatric TBI is required.…”
Section: Discussionmentioning
confidence: 92%
“…Ewing-Cobbs et al (2004) employed a transformation span (Digit Span Backward) task to assess the CE, which did not predict performance on arithmetic and reading comprehension after controlling for the duration of impaired consciousness and SES. Catroppa and Anderson (2007), who examined the storage components only, did not find an association between the performance of children with mild-to-severe TBI on measures of PL and VSSP and tests of reading and mathematics. Further research examining each of the components of WM and their contribution to different academic skills after pediatric TBI is required.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Anderson (2002, 2007) reported greater deficits on memory tasks, irrespective of modality in severe TBI in the acute (6 to 12 months post-injury) stage, in comparison to mild and moderate TBI. However, at 5 years post-injury, in the same sample of children, severe TBI was associated with decreased complex auditory-verbal memory performance, although children did not display impairment on immediate, working, or complex visual-spatial memory (Anderson & Catroppa, 2007). While recent literature suggests there is an increased risk for long-term verbal memory deficits in TBI, as noted, others have suggested that deficits in speed of information processing may be primarily responsible for the verbal learning deficits noted in pediatric TBI (Donders & Minnema, 2004).…”
Section: Examining Predictors Of Outcome On Memory and Learningmentioning
confidence: 77%
“…However, when an examination of verbal memory is coupled with a valid instrument of visual memory, a more comprehensive description of impairment emerges. Some studies have suggested a relative vulnerability of visual memory processes in some cases (Levin et al, 1988;Lowther & Mayfield, 2004) while others have reported a greater loss of verbal memory (Anderson & Catroppa, 2007;Hawley, Ward, Magnay, & Mychalkiw, 2004). For example, the increased vulnerability of visual memory functioning was suggested in an earlier study by Levin and colleagues (1988) for which they reported initial and persistent visual recognition memory deficits in both children and adolescents at 1 year post-injury, while verbal memory impairment persisted only in the adolescents.…”
Section: Assessment Of Memory and Learning In Pediatric Tbimentioning
confidence: 85%
“…Moreover, performance on measures such as phonological processing and verbal memory surfaced as important predictors of academic performance, suggesting potential areas of intervention to support long-term academic success. Catroppa and Anderson (2007) studied the relationship between memory and academic functioning at 2 years postinjury in pediatric TBI. Consistent with the studies described above, children with severe TBI displayed greater impairment on learning and memory.…”
Section: Predictors Of Memory Learning and Academic Functioningmentioning
confidence: 99%